Contribution of hot-melt extrusion technology to advance drug delivery in the 21st century. (3rd March 2016) - Tiwari, Roshan V.; Patil, Hemlata; Repka, Michael A.
ABSTRACT: Introduction : Hot-melt extrusion (HME) technology is applied successfully in the plastic, rubber and food industry. HME has also emerged as an important technology for drug delivery applications in pharmaceutical research and manufacturing because of its process automation and low-cost scale-up properties, which reduce labor costs and capital investment. There are a number of commercial FDA-approved HME-derived products, signifying the commercial feasibility of this novel technique in drug delivery applications. HME is a highly efficient, solvent-free continuous processing technique for the development of solid dispersions; thus, research efforts to develop sustained, modified and targeted drug delivery systems to improve the solubility and bioavailability of poorly water-soluble active pharmaceutical ingredients (APIs) are of interest. Areas covered : This review focuses on both the innovations and applications of HME in the production of pharmaceutical formulations, and on the significant findings of the general principles regarding formulation and process development via HME as described in published articles. Expert opinion : Challenges faced by pharmaceutical companies to produce efficient drug formulations may be partly overcome by HME's advantages – high drug-loading capacity, good content uniformity, cost-effectiveness, and ease of processing scale-up. Nevertheless, HME's high processing temperatures may be an obstacle if adequate knowledge about the product's formulation is lacking.